Normal mesenteric lymph ameliorates lipopolysaccharide challenge-induced spleen injury - Zhang,Li-min (2015)
PURPOSE: This study was conducted to investigate the effect of normal mesenteric lymph (NML) from mice on the spleen injury induced by lipopolysaccharide (LPS) challenge.METHODS: Mice in the LPS and LPS+NML groups received an intraperitoneal injection of LPS (35 mg/kg) and kept for 6 h.. The mice in the LPS+NML group received NML treatment at 1 h after LPS injection. Afterward, the splenic morphology, the levels of lipopolysaccharide-binding protein (LBP), cluster of differentiation 14 (CD14), phosphorylation mitogen-activated protein kinases (MAPKs), and inflammatory mediators in splenic tissue were investigated.RESULTS:LPS injection induced spleen injury, increased the levels of LBP, CD14, tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6), and interferon γ (IFN-γ), and decreased the IL-4 content in the spleen. By contrast, NML treatment reversed these changes. Meanwhile, the LPS challenge decreased the phosphorylation levels of p38 MAPK, extracellular regulated protein kinases 1/2, and c-Jun N-terminal kinase (JNK). Moreover, the phosphorylation levels of p38 MAPK and JNK were further decreased by the NML administration.CONCLUSION:rRdThe normal mesenteric lymph treatment alleviated lipopolysaccharide induced spleen injury by attenuating LPS sensitization and production of TNF-α, IL-6, and IFN-γ.